PERLINDUNGAN KONSUMEN MENURUT UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN DAN HUKUM ISLAM - Rindani, Liantika Rizky (UIN Sunan Kalijaga Yogyakarta, 2017)
Consumers are often aggrieved parties in various fields, whether in health care, economic transactions, transportation services, as well as freight forwarding services. To minimize this, pemeritah has issued a law guaranteeing the rights of consumers, namely Law No. 8 of 1999 on Consumer Protection. With the existence of this law then any aggrieved consumers are given the right to claim damages to the party that had led to the losses. However, in practice, not all agencies providing services to consumers have applied this law to the fullest. In this context, PT Pos Indonesia (Persero) Merjosari Malang is one example. Here, PT Pos Indonesia Merjosari Malang has indeed enacted and applied this law; In the sense that the postal party has assigned its responsibility to the consumer by providing compensation for the loss suffered by the consumer. However, the accountability of the post to the consumer looks not maximized, because there are still consumers who can not claim losses suffered. Thus the responsibilities made by the postal entities do not fully comply with the laws of consumer protection as well as Islamic law